Predictors of Perioperative Complications in Higher Risk Children after Adenotonsillectomy for Obstructive Sleep Apnea: A Prospective Study. (December 2014) - Thongyam, Anchana; Marcus, Carole L.; Lockman, Justin L.; Cornaglia, Mary Anne; Caroff, Aviva; Gallagher, Paul R.; Shults, Justine; Traylor, Joel T.; Rizzi, Mark D.; Elden, Lisa
Objective: Retrospective studies have limitations in predicting perioperative risk following adenotonsillectomy in children with obstructive sleep apnea syndrome (OSAS). Few prospective studies exist. We hypothesized that demographic and polysomnographic (PSG) variables would predict respiratory and general perioperative complications. Study Design: Prospective, observational cohort study. Setting: Pediatric tertiary center. Subjects and Methods: Consecutive children undergoing adenotonsillectomy for OSAS within 12 months of PSG were evaluated for complications occurring within 2 weeks of surgery. Results: There were 329 subjects, with 27% <3 years old, 24% obese, 16% preterm, and 29% with comorbidities. In this higher risk population, 28% had respiratory complications (major and/or minor), and 33% had nonrespiratory complications. Significant associations were found between PSG parameters and respiratory complications as follows: apnea hypopnea index (rank-biserial correlation coefficient [ r ] = 0.174, P = .017), SpO2 nadir ( r = −0.332, P < .0005), sleep time with SpO2 <90% ( r = 0.298, P < .0005), peak end-tidal CO2 ( r = 0.354, P < .0005), and sleep time with end-tidal CO2 >50 mm Hg ( r = 0.199, P = .006). Associations were also found between respiratory complications and age <3 years ( r = −0.174, P = .003) or black race ( r = 0.123, P = .039). No significant associations existed between PSG parameters and nonrespiratory complications. A model using age <3 years, SpO2 nadir, and peak CO2 predicted respiratory complications better than the American Academy of Pediatrics or American Academy of Otolaryngology—Head and Neck Surgery Foundation guidelines but was imperfect (area under the curve = 0.72). Conclusion: Thus, PSG predicted perioperative respiratory, but not nonrespiratory, complications in children with OSAS. Age <3 years or black race are high-risk factors. Present guidelines have limitations in determining the need for postoperative admission.